The Determinants of Non-Performing Financing (NPF) in Islamic Commercial Banks in Indonesia - Estiawan, Andika Bayu; Asrori, Asrori (Accounting Analysis Journal, 2021)
This research aims to analyze the effect of total financing, Financing to Deposit Ratio (FDR), Good Corporate Governance (GCG) on Non-Performing Financing (NPF) with inflation as a moderating variable. This research population is Islamic commercial banks for the period 2012-2018, which are registered with the Financial Services Authority. Research samples are obtained through a purposive sampling technique. According to the purposive sampling technique, some 11 Islamic Commercial Banks obtained 77 units of analysis. This research’s analytical method is multiple regression analysis and the absolute difference value. This research proves that GCG has a negative and significant effect on NPF, while Total Financing and FDR have no significant effect on NPF. Meanwhile, inflation did not moderate total financing, FDR, and NPF. Referring to the research results that have been described, the conclusion that the writer can compile is that the quality of GCG in a company is getting better, proven to reduce the level of NPF. Thus, Islamic Commercial Banks are expected to optimize the role of GCG to reduce the NPF level. Keywords: Non-Performing Financing; Islamic Commercial Banks; Financing; Inflation